(untitled) (Journal of Scientific Research, 2013)
The temperature at which the ferrite is sintered critically depends on the chemical composition. The electromagnetic properties are dependent on the densification and microstructure. Substitutions and addition of sintering aids is an attractive approach to enhance the electromagnetic properties. Various compositions in the system Ni1-x-yCuxZnyFe2O4 were investigated. Cu is used to decrease the sintering temperature. However, Cu decreases the resistivity, which is not desirable for its high frequency applications. So, optimization of Cu content is necessary. Different ranges of electromagnetic properties have been reported with various Zn concentrations. Optimization of Zn concentration with respect to Ni and Cu is essential to achieve desirable electromagnetic properties. Influence of rare earths has also been reported. The investigations showed an improved densification in Ni-Zn and increased permeability in Cu-Zn ferrite by Sm substitution. La substitutions showed an improved resistivity in Ni-Zn ferrites. Similarly, these substitutions may improve the electromagnetic properties in Ni-Cu-Zn ferrites. V2O5, MoO3 and Bi2O3 were reported to be the most widely used sintering additives. Bi2O3-WO3 and V2O5-MoO3 mixed additives were better than the individual additives in Ni-Cu-Zn ferrite, respectively. Further research is needed on the mixed sintering additives Keywords: Additives; Ferrite preparation; Ni-Cu-Zn ferrite; Rare Earth; Sintering aids. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.12434 J. Sci. Res. 5 (2), 215-233 (2013)